A haunted society: Old age pensions in Iceland from a gender perspective - Steinunn Rögnvaldsdóttir 1986- (2012)
The topic of this thesis is old age pensions from a gender perspective. The research is quantitative; statistics on the economic situation of both genders are presented, and conclusions drawn about older women’s situations in regard to pensions and the future prospects of women of working age. Conclusions drawn from the statistical analysis are put into context with the theoretical framework of the thesis: women-friendly welfare states versus patriarchal states, (in)justice in marriage, economic citizenship, Nancy Fraser’s “universal caregiver” model, and the dilemma of dichotomy concerning women-friendly policies. The results show that women have earned less occupational and supplemental pensions and depend more on the basic pension of social security. Although women’s labor market participation has increased, the gender pay gap, unpaid labor in homes and women’s fewer employment working hours will result in the extension of the labor market gender discrimination into old age. The research found no direct discriminating factors at work in the Icelandic pension funds, although their structure is fundamentally male biased. The thesis suggests implications to create a more women friendly pension system, based on multi-national research, the analysis of the Icelandic pension system and statistical information on older women and men’s economic situation in Iceland. Umfjöllunarefni þessarar ritgerðar eru ellilífeyrismál útfrá kynjasjónarmiði. Rannsóknin er meginleg; skoðaðar eru tölur um efnahagslega stöðu og lífeyri eftir kyni og ályktað útfrá þeim bæði um stöðu eldri kvenna á ellilífeyri í dag, og framtíðarhorfur kvenna sem nú eru á vinnualdri. Niðurstöður eru settar í samhengi við kenningar um kvenvænleg velferðarríki og feðraveldi, valda(ó)jafnvægi innan hjónabands, efnahagslegan þegnrétt og kenningar Nancy Fraser um „universal caregiver“. Einnig er niðurstöðum fléttað saman við gagnrýni á tvíhyggju. Niðurstöður leiddu í ljós að konur hafa unnið sér inn minni tekjur hjá lífeyrissjóðum og með ...